Scintillator Nanocomposite
Patent Information
- Application Number
- JP2018524334
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2015-11-19
- Filing Date
- 2016-11-07
- Publication Date
- 2024-12-26
- Estimated Expiration
- 2036-11-07
AI Technical Summary
Existing scintillator nanocomposites face challenges in achieving uniform diffusion and conformability due to the use of dispersing agents and solvents that need to be removed, leading to internal damage, nanoparticle aggregation, and reduced transparency, especially with cerium dopants causing surface defects.
A method involving a stable suspension of nanoparticles in a precursor of the matrix material, using glycol as a dispersant, followed by curing at elevated temperature and pressure to form a polymeric matrix, eliminating the need for solvent removal and reducing defects.
Results in high-quality, transparent scintillator nanocomposites with improved homogeneity and reduced defects, suitable for radiation detectors and imaging systems.
Abstract
Description
[Technology Field]
[0001] The present invention generally relates to methods for producing scintillator nanocomposites, scintillator nanocomposites, products having scintillator nanocomposites, methods for producing transparent scintillators, transparent scintillators, radiation detectors, and imaging systems. [Background technology]
[0002] Radiation detection materials, such as phosphors, are used in many applications, for example, as scintillator materials in security or medical scanners (e.g., X-ray, CT, PET, or SPECT scanners). These materials are typically used in single-crystal form, and their size is limited due to limitations in synthesis methods.
[0003] Nanoscale composites represent an interesting approach to developing radiation detectors, circumventing the limitations of single crystals. Composite materials can be produced in a variety of shapes and sizes. Similarly, the cost of scintillator fabrication can be significantly reduced. Furthermore, composites filled with nanoscale filler materials have a higher surface-to-volume ratio than conventional composites with microscale fillers. [Overview of the Initiative] [Problems that the invention aims to solve]
[0004] The scintillator nanocomposite 10 is generally prepared by dispersing nanoparticles 12 having scintillation properties in powder form in a dispersant or prepolymer to form a polymer matrix 11 to which the nanoparticles are distributed (see Figure 1a for the composition of the scintillator nanocomposite 10 having well-dispersed nanoparticles).
[0005] However, a major limitation to the use of nanocomposite materials in radiation detection is the extreme difficulty in achieving uniform diffusion and compatibility in known scintillator nanocomposites (see Figure 1b). This is partly due to the use of dispersants and / or solvents that need to be removed before polymerization in order to allow the nanoparticle powder to be properly dispersed in the prepolymer. However, this is an extremely difficult process, and any unwanted material remaining in the scintillator can cause internal damage to the matrix structure, such as inclusions and / or voids, which degrade the transparency and quality of the scintillator nanocomposite. Furthermore, adding large amounts of nanoparticles to any matrix material may be difficult. More dispersants and / or solvents may be required, making their removal even more difficult and thereby exacerbating the problem. Higher nanoparticle content leads to increased nanoparticle aggregation in the composite.
[0006] Furthermore, for many optical applications such as radiation detectors, the powder size of nanoparticles is limited to the 10-50 nm range. Such particles have a light scattering coefficient small enough to (partially) obtain transparent nanocomposites. However, such small-sized nanoparticle powders usually aggregate strongly, resulting in larger aggregate structures 13, which do not result in the desired transparency. In International Publication No. 2009 / 054946, aggregation of nanophosphor scintillators in matrix materials is addressed by surface modification of nanophosphor particles using ligands that allow for the separation of surface charges or direct binding of chemicals to the matrix material. However, such nanoparticles need to be specifically modified, which makes their manufacture more complex and makes their particles more effective. Furthermore, ligands can affect scattering and absorption properties.
[0007] In addition, dopants used in the scintillator material that are present on the surface of the scintillator material (e.g., cerium dopant) increase the formation of surface defects 15, which reduces luminescence and therefore results in a lower quality scintillator.
[0008] One object of the present invention is to obtain high-quality transparent scintillator composites from nanoparticle powders and a manufacturing process that gives a lower yield of less complex, high-quality scintillator materials. Other objects and advantages will be mentioned throughout this description. [Means for solving the problem]
[0009] This objective is achieved by a method for producing a scintillator nanocomposite having scintillating properties and nanoparticles having a diameter of 10 to 50 nanometers, and a first matrix material, the method comprising the steps of adding nanoparticles to a dispersion medium to form a stable suspension, wherein the dispersion medium is a precursor of the first matrix material, and curing the dispersion medium to form the first matrix material. By using a precursor of the first matrix material as a dispersant, the precursor does not need to be removed, thus eliminating an energy-consuming process step, and more importantly, a processing step that would result in defects in the final product that reduce the transparency of the scintillator nanocomposite. For this reason, the nanocomposite obtained by the method of the present invention is of higher quality than nanocomposite obtained by known manufacturing methods.
[0010] According to another preferred embodiment of the present invention, the scintillator nanoparticles are garnet nanoparticles, preferably cerium-doped nanoparticles, most preferably Y3Al5O 12 :Ce(YAG:Ce) nanoparticles, (Lu,Gd)3Al5O 12 :Ce(LGAG:Ce) nanoparticles, or (Lu,Gd)3(Al,Ga)5O 12These are nanoparticles selected from the group of Ce(LGGAG:Ce) nanoparticles. These are garnets that are known to be very suitable, for example, in medical imaging or security imaging.
[0011] In a preferred embodiment of the present invention, the dispersion medium is glycol, preferably 1,4-butanediol. This is a particularly suitable precursor for polyurethane matrix materials.
[0012] In a preferred embodiment of the present invention, a second dispersion medium is mixed with the first dispersion medium before adding nanoparticles or before a stable suspension. The second dispersion medium is a precursor of the second matrix material. In some examples, the second matrix material can be used to achieve other improved properties, such as optical or mechanical properties. The first and second matrix materials can be cured into a single matrix material (e.g., copolymer). Here again, it is advantageous to use a dispersant that reacts to form the matrix material instead of one that needs to be removed.
[0013] In a preferred embodiment of the present invention, the first or second matrix material is a polymer material, preferably selected from the group of polyesters such as polyurethane, polybutylene terephthalate, unsaturated polyester resin, aromatic polyamide, aromatic polyimide, and polystyrene, or polysulfone.
[0014] Polymers are often very suitable for processing, compatible with nanoparticles, and offer a good selection of precursors or precursor synthesis materials with optical properties that make them suitable for various optical applications (e.g., radiation imaging).
[0015] According to another preferred embodiment of the present invention, curing is carried out at a high temperature, preferably between 220 and 250 degrees Celsius, more preferably about 225 degrees Celsius, and / or at a high pressure, preferably above 20 bar, most preferably about 40 bar, and / or for at least 24 hours. These are good reaction conditions, especially for polymer matrix materials such as polyurethane.
[0016] In a preferred embodiment of the present invention, the resulting nanocomposite has a polyurethane gel matrix material. Polyurethane can be relatively easily molded into many different shapes for many applications.
[0017] The present invention further aims to produce and obtain a transparent scintillator having improved quality and that can be used in a radiation detector, for example, which can be applied in an imaging system.
[0018] Other views and embodiments of the present invention will be understood by those skilled in the art by reading and understanding the following detailed description. Many additional benefits and advantages will become apparent to those skilled in the art by reading the following detailed description of preferred embodiments.
[0019] The present invention is illustrated by the accompanying drawings. [Brief explanation of the drawing]
[0020] [Figure 1a] Schematic diagram of a well-dispersed scintillator nanocomposite. [Figure 1b] Figure showing a scintillator nanocomposite with several defects. [Figure 2] A flowchart combining a method for generating a scintillator nanocomposite, a method for generating a transparent scintillator, and a method for constructing a radiation detector according to the present invention. [Figure 3] (a) and (b) are graphs showing the optical properties of the transparent nanocomposite according to the present invention. [Figure 4] Schematic diagram of a radiation detector module according to the present invention. [Figure 5] Schematic diagram of an exemplary imaging system according to the present invention.
Mode for Carrying Out the Invention
[0021] The present invention can take the form of various components and combinations of components, as well as various process operations and combinations of process operations. The drawings are only for exemplifying the preferred embodiments and should not be construed as limiting the present invention. For better visualization, certain features may be omitted or not drawn to scale.
[0022] Some types of scintillator nanoparticles (e.g., garnet-based nanoparticles) are known. The present invention is described with respect to some specific scintillating nanoparticles by way of example, but is not limited thereto, and those skilled in the art will know how to prepare and use other types of scintillator nanoparticles in the same manner.
[0023] To obtain the scintillator nanocomposite 10, the scintillator nanoparticles 12 need to be embedded in a matrix 11, which is here described using a polymer matrix. As described above, known scintillator nanocomposites are prepared by dispersing nanoparticles in a precursor material that is shaped into a matrix, such as a monomer that can be (co)polymerized into a polymer matrix. Non-polymer precursors are possible, such as inorganic precursors that can be cured in an inorganic matrix material having a glass-like structure.
[0024] The refractive index of scintillator nanoparticles and matrices must be adapted to be suitable for optical applications, such as radiation detectors. However, this is not a trivial matter, as nanoparticles typically have a higher refractive index than most polymers. For example, Y3Al5O 12 Ce nanoparticles have a refractive index of 1.8, while polymers typically have a refractive index of 1.7 or less (for example, polyurethane has a refractive index of approximately 1.5). High refractive index polymers are rare and expensive. The refractive index of the polymer matrix can be increased by adding inorganic particles such as TiO2 or ZrO2, but this requires a very large amount of inorganic material, which will result in even more defects in the nanocomposite and thus affect the problem that this invention seeks to solve. A better solution is to use scintillator nanoparticles with very small diameters. Since the scattering intensity depends on the sixth power of the particle diameter (Rayleigh equation), only particles with a size smaller than the wavelength of visible light will not interfere with the incident light, and consequently, the composite will not appear cloudy. In particular, nanoparticles smaller than 50 nm in the matrix appear transparent to the human eye.
[0025] Unfortunately, such small nanoparticles have a strong tendency to form aggregates 13 due to van der Waals forces resulting from their relatively large surface area. These aggregates 13 typically increase in size to several hundred nanometers and behave like submicron particles that scatter incident light, reducing the transparency of the nanocomposite, which is highly detrimental to the transparency and quality of the scintillator nanocomposite.
[0026] The present invention presents a manufacturing method that yields a transparent scintillator nanocomposite, which distributes nanoparticles smaller than 50 nm more homogeneously in a matrix while simultaneously reducing defects caused by dispersants or solvents used in known methods for producing nanoparticle dispersions used in the manufacture of scintillator nanocomposites.
[0027] First, scintillator nanoparticles are prepared using one of the many known methods for synthesizing scintillator nanoparticles (101).
[0028] Next, the nanoparticles are dispersed in an organic medium (102). It is an insight of the present invention that this organic medium is a precursor material for forming the matrix material (at least a portion thereof), and is, for example, a monomer that can be (co)polymerized into a polymer matrix. The organic material and the resulting matrix material have many requirements, which makes selecting a suitable organic medium complicated. Firstly, the organic medium disperses the scintillator nanoparticles to form a stable suspension with a solid content of up to 50%. Secondly, the resulting matrix material (e.g., polymer) must be radiation-curable, compatible with any other material present in the nanocomposite (e.g., polymers that can or cannot form copolymers), and have a refractive index compatible with such material, preferably not too expensive or difficult to obtain. Surprisingly, glycols and in particular 1,4-butylene glycol [HO-(CH2)4-OH] have been found to possess the necessary properties for use as an organic medium that can be (co)polymerized into suitable polymer matrix materials such as polyurethane or polyester. 1,4-butanediol is Ce 3+ Furthermore, because it has a stabilizing effect on nanoparticles, 1,4-butanediol is even more attractive for use in cerium-doped scintillator materials. This subsequently reduces surface defects 15 in the nanocomposite 10 caused by cerium migration.
[0029] For example, alternative precursor materials include precursors of aromatic polyamides or aromatic polyimides such as dianhydrides, diamines, N,N-dimethylacetamide (DMAc), or N-methylpyrrolidinone (NMP); precursors of polystyrene such as 4,4'-azobis-4-cyanovaleric acid (ACVA) or polyvinylpyrrolidone (PVP); or precursors of polysulfones such as diphenols (bisphenol-A or 1,4-dihydroxybenzene) and bis(4-chlorophenyl)sulfone. As mentioned above, inorganic precursors are also possible.
[0030] A suspension of the precursor material and nanoparticles is cured into a matrix material (103). To polymerize the glycol, for example to form a polyurethane or polyester, it is necessary to add another monomer (e.g., isocyanate or dicarboxylic acid). This polymerization mechanism is generally known. Other reagents, such as comonomers, can be used to form copolymers and catalysts. Dibutyltin dilaurate (DBTDL) is preferred as a catalyst because it is known to shorten the reaction time. Using 1,6-diisocyanatohexane (HDI) as an isocyanate source is preferred because it can increase transparency and increase the amount of nanoparticles in the matrix. After polymerization, the presence of nanoparticles does not significantly affect the reaction conditions or the resulting polymer, except that the nanoparticles 12 are embedded in the polymer matrix 11 in a homogeneous manner with fewer or at least smaller aggregates 13 and less matrix collapse 14 and fewer surface defects 15 (e.g., as schematically shown in Figure 1a).
[0031] The polymerization reaction is carried out in a pressurized oven such as an autoclave. The temperature must be close to or above the boiling point of the organic medium. For 1,4-butylene glycol, this provides a temperature window of 220 to 250 degrees Celsius, with a preferred working temperature of 225 degrees Celsius. A high pressure of at least 20 bar, preferably about 40 bar, must be applied, and furthermore, in order to obtain a well-cured and well-dispersed scintillator nanocomposite, the reaction must be maintained under these conditions for at least 24 hours.
[0032] To obtain high-quality nanocomposites, all starting materials must be dehydrated and degassed (preferably at a temperature of 100 to 150°C) to avoid inclusions or defects in the nanocomposites. In particular, the presence of water makes the polymerization reaction too rapid, making it difficult to control the nanoparticles, and thus making it very difficult, or even impossible, to obtain scintillator nanocomposites.
[0033] Since defects are not caused by insufficient or ineffective solvent removal, nanoparticle composites with improved transparency and quality can be obtained. This can be further improved by melting the resulting nanocomposite (104) and injection molding the molten composite (105). Rapid dissolution and rapid cooling in this process can reduce further defects. This is particularly effective when the nanocomposite contains a polymer having a block structure in which harder and softer segments are bonded together, such as in the case of polyurethane.
[0034] The segments have high polarity and therefore a strong tendency to aggregate, resulting in the formation of a (pseudo) crystalline structure that reduces transparency; therefore, the transparency before injection molding is not yet optimal. Crosslinking between segments disappears with heating and injection, preventing the development of crystallits, and as a result, a significantly improved transparency of the nanocomposite is obtained.
[0035] The improved nanocomposites of the present invention can be further processed for use in various applications, such as radiation detectors. Figure 4 shows a highly simplified diagram of a radiation detector in which a scintillator 31 is optically mounted on a photodiode 32 mounted on an integrated circuit 33. Vertical configurations, other layers, pixelated detectors, and other configurations are further conceivable in the context of the present invention.
[0036] The radiation detector 30 can then be incorporated into an imaging system 40 such as an X-ray imaging system, a CT imaging system 40 ( schematically shown as an example in Figure 5), a PET imaging system, or a SPECT imaging system. The improved nanocomposite can be further processed like known nanocomposites, and the structure 106 of the radiation detector can be produced using known techniques.
[0037] Example 1. Y3Al5O 12 : 1% Ce nanoparticles (~20 vol.%) Polyurethane filled with 11.498 g of aluminum isopropoxide, 11.336 g of yttrium acetate hydrate, and 0.111 g of cerium acetate hydrate was mixed with a solvent mixture of 1,4-butylene glycol and diethylene glycol in a mass ratio of 9:1.
[0038] The colloidal solution was stirred on a hot plate for 3 hours by gentle heating at 50 degrees Celsius. After the mixture was homogenized, it was poured into a high-pressure autoclave vessel. The air present in the autoclave was washed with argon, and then the mixture was heated to 225°C for 60 hours at a heating rate of 1.5°C / min. After the process was complete, the mixture was cooled to obtain a translucent yellowish suspension.
[0039] Next, 9 g of the resulting dehydrated suspension was rapidly mixed with 16 g of dehydrated 1,6-diisocyanatohexane and 1 drop of dibutyltin dilaurate. The viscous material was poured into a Teflon mold and held in a 60°C oven for 8 hours to obtain nanocomposite particles.
[0040] The nanocomposite particles were introduced into an injection mold, melted at 210 degrees Celsius, and immediately cooled within the mold.
[0041] Figure 3(a) shows the transmittance T, reflectance R, and absorptance A of the resulting transparent YAGCe-polyurethane nanocomposites. Figure 3(b) shows the emission of the obtained nanocomposites under excitation at 450 and 360 nm. The scintillators in this example are transparent at visible wavelengths but absorb wavelengths of X-rays, thereby making them suitable for use in CT and other X-ray radiation detectors. For PET, the absorption should be at 511 keV. For other purposes, absorption of ultraviolet or other wavelengths may be required. By selecting the correct scintillating nanoparticles, the absorption and emission wavelengths can be set, for example, using nanoparticles based on Eu or Tb.
[0042] Considering the stoichiometric differences in quantity, LGAG:Ce(at least Lu2Gd1Al5O 12 :Confirmed with 1%Ce) and LGGAG:CE (at least Lu2Gd1Al4Ga1O 12 Similar results were obtained for 1% Ce (confirmed). Garnet scintillators such as LGGAG:Ce are particularly difficult to obtain in terms of sufficient transparency and quality. The method of the present invention provides nanocomposite scintillators with high transparency and high quality for these types as well.
[0043] It is also possible to obtain a gel, for example a polyurethane gel, as a matrix material for a scintillator material. In particular, when the nanoparticles have luminescent properties, several interesting applications can be created using gel-based nanocomposites: for example, flexible luminescent sheets (e.g., for safety applications, fabrics, etc.) or health applications (e.g., for treating skin diseases with light. In this case, the luminescence is optically excited). They can also be applied to certain toys. Furthermore, they can have a luminescent function and be used in the same fields as known (polyurethane or other) gels: luminescent computer mouse pads / keyboard wrist rests, luminescent bicycle parts, luminescent motorcycle seats, luminescent shoe insoles, luminescent padding parts for medical devices, luminescent adhesive pads for holding mobile phones and tablet computers, any conformal luminescent layer for covering products, and others.
[0044] Example 2. Lu2Gd1Al5O 12 : Polyurethane gel (PU gel) filled with 1% Ce nanoparticles (˜35 vol.%) 6.008 g of aluminum isopropoxide, 7.529 g of lutetium acetate hydrate, 3.350 g of gadolinium acetate hydrate and 0.104 g of cerium acetate hydrate were mixed with a solvent mixture of 1,4-butylene glycol and diethylene glycol in a mass ratio of 9:1. The colloidal solvent was stirred on a hot plate for 3 hours with gentle heating at 50 °C.
[0045] After the mixture was homogenized, it was poured into a high-pressure autoclave container. The air present in the autoclave was purged with argon. The mixture was heated to 225 °C at a heating rate of 1.5 degrees / min for 60 hours. After the process was completed, the mixture was cooled and a translucent yellowish suspension was obtained.
[0046] The resulting 5 g of dehydrated suspension was rapidly mixed with 6.5 g of polymer MDI mixture (a mixture of oligomeric polyisocyanates) and an MDI isomer (isocyanate (1-isocyanate-4-[(4-isocyanatephenyl)methyl]benzene)). The resulting viscous polyurethane gel was then poured into a Teflon mold.
[0047] Nanocomposites can be produced in any shape or form (e.g., sheets, powders, molded articles, foils, etc.) using the method of the present invention, provided that the precursor material is sufficiently dispersed with nanoparticles and (co)polymerized into an optically compatible matrix material for the scintillating nanoparticles. Curing is not limited to curing by heating. Other curing reactions, such as ultraviolet polymerization and others known to those skilled in the art, are also intended.
[0048] The nanoparticle composites of the present invention can be applied in various embodiments known to those skilled in the art, such as deposition, coating, and printing.
[0049] The nanoparticle composites of the present invention can be molded by injection molding or other molding techniques, 3D printing and other techniques known to those skilled in the art.
[0050] Although the present invention is illustrated and described in detail in the drawings and the above description, such illustrations and descriptions should be considered illustrative or descriptive, not restrictive. The present invention is not limited to the disclosed embodiments.
[0051] In this application, the term "about" is considered to encompass values that are 10% lower or higher than a given value.
[0052] Other modifications to the disclosed embodiments can be understood and achieved by those skilled in the art in carrying out the claimed invention, based on a review of the drawings, disclosures, and appended claims. In the claims, the words “comprising” do not exclude other components or steps, and the indefinite articles “a” or “an” do not exclude plurality. A single processor or other unit can perform the functions of several items enumerated in the claims. The mere fact that certain means are enumerated in mutually different dependent claims does not imply that combinations of these means cannot be used advantageously. Computer programs can be stored / distributed on suitable media such as optical storage media or solid media supplied together with or as part of other hardware, and can also be distributed in other forms, such as via the Internet or other wired or wireless telecommunications systems.
[0053] Any reference numeral in a claim should not be construed as limiting the scope of the claim.
Claims
1. 1. A method for producing a scintillator nanocomposite having scintillation properties and nanoparticles with a diameter of 10 to 50 nanometers and a first matrix material, comprising: To form a stable suspension, Glycol adding the nanoparticles to the Glycol is a precursor of the first matrix material; to mold the first matrix material. Glycol and curing the The method according to claim 1,
2. The nanoparticles are garnet nanoparticles, preferably cerium doped nanoparticles, most preferably Y3Al5O 12 : Ce nanoparticles, (Lu,Gd)3Al5O 12 2. The method of claim 1, wherein the nanoparticles are selected from the group of (LGGAG:Ce) nanoparticles or (LGGAG:Ce) nanoparticles.
3. 3. The method according to claim 1 or 2, wherein the first matrix material is a polymeric material, preferably selected from the group consisting of polyurethane, polybutylene terephthalate, unsaturated polyester resin, aromatic polyamide, aromatic polyimide, polystyrene, polysulfone and polyester.
4. The glycol is 4. The method according to claim 1, wherein the diol is 1,4-butanediol.
5. A second dispersion medium is added to the mixture before adding the nanoparticles or before obtaining the stable suspension. Glycol 6. The method of claim 1 , wherein the second dispersion medium is a precursor of a second matrix material.
6. 6. The method according to claim 5, wherein the second matrix material is a polymeric material, preferably selected from the group consisting of polyurethane, polybutylene terephthalate, unsaturated polyester resin, aromatic polyamide, aromatic polyimide, polystyrene, polyester, and polysulfone.
7. The method of claim 6 , wherein the curing step produces a copolymer of the first matrix material and the second matrix material.
8. 8. The method according to any one of claims 1 to 7, wherein the curing is carried out at elevated temperature, preferably between 220 and 250 degrees Celsius, more preferably at about 225 degrees Celsius, and / or at high pressure, preferably at a pressure higher than 20 bar, most preferably at a pressure of about 2 to 40 bar, and / or for a period of at least 24 hours.
9. The method according to any one of claims 1 to 8. Available from Scintillator nanocomposites.
10. 10. The scintillator nanocomposite of claim 9, wherein the first matrix material is a polyurethane, more preferably a polyurethane gel.
11. 11. An article comprising the scintillator nanocomposite of claim 9 or 10.
12. 1. A method for producing a transparent scintillator, comprising the steps of: Dissolving the nanocomposite obtained by the method according to any one of claims 1 to 9; injection molding the molten nanocomposite; The method according to claim 1,
13. A transparent scintillator obtained by the method of claim 12.
14. A radiation detector comprising the transparent scintillator according to claim 13.
15. 15. An imaging system comprising a radiation detector according to claim 14.
